The chaotic behavior among the oil prices, expectation of investors and stock returns: TAR-TR-GARCH copula and TAR-TR-TGARCH copula - Bildirici, Melike (SPRINGEROPEN, 2019)
This paper has two aims. The first one is to investigate the existence of chaotic structures in the oil prices, expectations of investors and stock returns by combining the Lyapunov exponent and Kolmogorov entropy, and the second one is to analyze the dependence behavior of oil prices, expectations of investors and stock returns from January 02, 1990, to June 06, 2017. Lyapunov exponents and Kolmogorov entropy determined that the oil price and the stock return series exhibited chaotic behavior. TAR-TR-GARCH and TAR-TR-TGARCH copula methods were applied to study the co-movement among the selected variables. The results showed significant evidence of nonlinear tail dependence between the volatility of the oil prices, the expectations of investors and the stock returns. Further, upper and lower tail dependence and co-movement between the analyzed series could not be rejected. Moreover, the TAR-TR-GARCH and TAR-TR-TGARCH copula methods revealed that the volatility of oil price had crucial effects on the stock returns and on the expectations of investors in the long run.
Keywords: Oil price; Expectations of investors; Stock returns; Chaos; Lyapunov exponent; Kolmogorov entropy; TAR-TR-GARCH and TAR-TR-TGARCH copula methods; MARKETS; SHOCKS; VOLATILITY; TIME; UNCERTAINTY; IMPACT; FEAR; DEPENDENCE; COUNTRIES; INFERENCE; Energy & Fuels; Engineering